Synthesis of AuAg/Ag/Au open nanoshells with optimized magnetic plasmon resonance and broken symmetry for enhancing second-harmonic generation. Issue 46 (22nd November 2021) - Zhou, Tao; Ding, Si-Jing; Wu, Zhi-Yong; Yang, Da-Jie; Zhou, Li-Na; Zhao, Zhi-Rui; Ma, Liang; Wang, Wei; Ma, Song; Wang, Si-Man; Zou, Jia-Nan; Zhou, Li; et al.
Abstract : The cooperation of magnetic and electric plasmon resonances in Au open nanoshells exhibits significant capability for second-harmonic generation (SHG) enhancement, and the SHG intensity is further enhanced by the Ag/Au and AuAg/Ag/Au open nanoshells. Abstract : The cooperation of magnetic and electric plasmon resonances in cup-shaped metallic nanostructures exhibits significant capability for second-harmonic generation (SHG) enhancement. Herein, we report an approach for synthesizing Au open nanoshells with tunable numbers and sizes of openings on a template of six-pointed PbS nanostars. The morphology of Au nanoshells is controlled by adjusting the amount of HAuCl4, and the characteristic shapes of pointed nanocaps, open nanoshells, and hollow nanostars are obtained. Owing to the collaboration of electric and magnetic plasmon resonance modes, the Au nanoshells exhibit significantly broadened and highly tunable optical responses. Furthermore, the morphology-dependent SHG of the Au nanoshells shows two maximal SHG intensities, corresponding to four-opening and one-opening Au nanoshells with appropriate opening sizes. Ag/Au and AuAg/Ag/Au open nanoshells were further investigated to achieve enhanced SHG. By adjusting the thickness of the Ag shell, the SHG intensity of Ag/Au open nanoshells reaches a maximum due to the gradient field at the AuAg bimetallic interface. After replacing the Ag shells with Au shells, the SHG intensity of AuAg/Ag/Au open nanoshells reaches a maximum due to further symmetry breaking. These findings provide a strategy to prepare colloidal metal nanocrystals with prospective applications ranging from nonlinear photonic nanodevices to biospectroscopy and photocatalysis.